Kesiapan Guru Ekonomi Dalam Menghadapi Online Learning Di Kota Ende - Stefanus Hubertus Gusti Ma; Helena Rosalia Parera; Sayful Amrin (Jayapangus Press, 2021)
This study aims to describe the readiness of economic teachers in facing online learning in Ende City. The sample in this study were all economics teachers in Ende City. This research method is quantitative descriptive research. The data collection technique used a questionnaire for primary data and secondary data using a documentation study. The data obtained were analyzed using the theoretical-descriptive approach and percentage techniques. The result showed that the readiness of economics teachers in facing online learning in Ende City ranged from 61,11 to 79,17 with the ready and very ready categories.